Relationship between screen-play scenarios' effectiveness and player classification in elite wheelchair basketball based on match results of Tokyo 2020 Paralympic Games - Yasuda, T.; Tachibana, K.; Mutsuzaki, H. (Frontiers in Sports and Active Living, 2024)
Background The competitiveness of wheelchair basketball has increased over time. However, screen-play, considered a vital offensive tactic in running basketball, is still poorly clarified. Therefore, this study aimed to clarify the impact of screen-play on scoring and game results in wheelchair basketball and assess the roles of each player classification (PC).